Pengaruh Kehandalan Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Dimediasi Kepuasan Pelanggan Pada Konsumen ELHA TRANS Indrapura - Nainggolan, Mika Rulas; Prayoga, Ardi Nanang; Purba, Rakhmawati (Management And Business Progress, 2024)
This study aims to determine the effect of reliability and service quality on customer loyalty mediated by customer satisfaction at ELHA Trans Indrapura. The effects we want to know are direct and indirect effects. This type of research is quantitative which is used to obtain or collect information data about a large population, usually using a relatively smaller sample. The sample used in this study was 96 respondents with a purposive sampling technique. The test tool used was SmartPLS Software version 3.0. From the results of this test, it can be concluded that Reliability does not have a significant effect on Customer Satisfaction. Service Quality has a significant effect on Customer Satisfaction. Reliability does not have a significant effect on Customer Loyalty. Service Quality does not have a significant effect on Customer Loyalty. Customer Satisfaction has a significant effect on Customer Loyalty. Customer Satisfaction is unable to mediate the effect between Reliability and Customer Loyalty. Customer Satisfaction is unable to mediate the effect between Service Quality and Customer Loyalty